DsTau: study of tau neutrino production with 400 GeV protons from the CERN-SPS - The DsTau collaboration; Shigeki Aoki; Akitaka Ariga; Tomoko Ariga; Sergey Dmitrievsky; Elena Firu; Dean Forshaw; Tsutomu Fukuda; Yuri Gornushkin; Ali Murat Guler; Maria Haiduc; Koichi Kodama; et al. (Journal of High Energy Physics)
Abstract In the DsTau experiment at the CERN SPS (NA65), an independent and direct way to measure tau neutrino production following high energy proton interactions was proposed. As the main source of tau neutrinos is a decay of Ds mesons, produced in proton-nucleus interactions, the project aims at measuring a differential cross section of this reaction. The experimental method is based on a use of high resolution emulsion detectors for effective registration of events with short lived particle decays. Here we present the motivation of the study, details of the experimental technique, and the first results of the analysis of the data collected during test runs, which prove feasibility of the full scale study of the process in future.